A genre analysis approach to the study of the translation of court documents - Borja Albi, Anabel (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2013)
This article describes an action research project on multilingual management and translation of court documents developed by the GENTT research group, which postulates that the notions of ‘textual genre’, ‘genre system’ and ‘meta-genre’ can be powerful tools for accessing and ‘reusing’ the linguistic and extra-linguistic information technical writers and translators need to manage specialised communication. To validate this hypothesis the criminal court genre systems of four countries (Germany, Spain, France and the United Kingdom) have been analysed and described from a legal-conceptual, discursive-textual and terminological perspective. The results of this contrastive analysis have been used as the basis for creating translation resources (both conceptual and linguistic), which have been organised into an online platform for translators of court documents. This platform is conceived as a knowledge system which will permit the ‘reusability’ of electronic translation resources. Our approach presents an integrative methodology for research into legal translation.